A Decade pf German support for workplace health : concepts - results - lessons learned - Papkalla, Ute (Deutsche Gesellschaft fur Internationale Zusammenarbeit (GIZ) GmbH BonnDE, 2012)
Gives an overview of German support in the form of public private partnerships and programmes for workplace interventions. Takes a deeper look into the concept of workplace programmes, summarising the experience acquired and the conceptual adaptations that were derived from the lessons learned. Analyses the results that were reported from the various partnerships and programmes conducted at company level. Highlights major milestones and provides an initial picture of the potential for expanding interventions to promote health in the workplace.